2023
DOI: 10.2141/jpsa.2023024
|View full text |Cite
|
Sign up to set email alerts
|

Effects of <i>Artemisia annua</i> L. Water Extract on Growth Performance and Intestinal Related Indicators in Broilers

Shiwei Guo,
Jiaxin Ma,
Yuanyuan Xing
et al.

Abstract: Artemisia annua L. is a natural herb with a variety of bioactive substances, which can play a variety of biological functions such as anti-inflammatory, antioxidant, antibacterial and antiviral, and can be used as a potential feed additive. The purpose of this study was to investigate the effects of different doses of Artemisia annua L. water extract (AAWE) on growth performance and intestinal related indicators in broilers. A total of 200 one-day-old Arbor Acre broilers were selected and randomly divided into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 44 publications
(62 reference statements)
1
1
0
Order By: Relevance
“…In the present study, dietary supplementation with AAP significantly increased BW on d 42, ADFI and ADG on d 36-42 in broilers. This is similar to our previous study, which found that dietary supplementation with Artemisia annua L. water extract increased the final body weight and feed efficiency of broilers (Guo et al, 2023). Furthermore, we found that oral administration of E. coli significantly reduced BW, ADG, and ADFI, and increased FCR of broilers in the present study.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In the present study, dietary supplementation with AAP significantly increased BW on d 42, ADFI and ADG on d 36-42 in broilers. This is similar to our previous study, which found that dietary supplementation with Artemisia annua L. water extract increased the final body weight and feed efficiency of broilers (Guo et al, 2023). Furthermore, we found that oral administration of E. coli significantly reduced BW, ADG, and ADFI, and increased FCR of broilers in the present study.…”
Section: Discussionsupporting
confidence: 93%
“…Artemisia annua L. ( A. annua ) is a species of Artemisia within the Asteraceae family, is widely distributed ( Ding et al, 2020 ) and is renowned for its rich variety of active substances, including sesquiterpenoids, flavonoids, coumarins, and volatile oils ( Das et al, 2020 ; Fu et al, 2020 ), consequently, it possesses numerous biological functions, including anti-inflammatory, antioxidant, antibacterial, antiviral, antitumor anti-malarial and immune regulatory activity ( Graham et al, 2019 ; Stan, 2020 ; Han et al, 2022 ; Chebbac et al, 2023 ; Wu et al, 2023 ). In poultry, previous studies have shown that A. annua aqueous extract can promote intestine immunity and antioxidant function ( Guo et al, 2022a ), inhibit the reproduction of E. coli and promote the proliferation of Lactobacillusla in broilers ( Guo et al, 2023 ). In addition, adding A. annua and its extracts into diets can effectively relieve heat stress, immune stress and oxidative stress in broilers ( Song et al, 2017 , 2018 ; Wan et al, 2017 , 2018 ; Choi et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%